Advanced Foam Roller with Tens / Mumtaz Husna Mustajab - Mustajab, Mumtaz Husna (2020)
Advanced Foam Roller with TENS SDN BHD is a supplier company which distribute a very multipurpose and high technology of foam roller. This product has been created to help people to improve their performance of lifestyle. This Advanced Foam Roller with TENS is a new product in the global market which this product is new an innovation. Advanced Foam Roller with TENS is the combination of product of vibrating foam roller and TENS in one. This product has many advantages compare to others common foam roller that have been sold in the market. This is because Advanced Foam Roller with TENS is multifunction product in order to help coaches, athletes, personal trainer, physiotherapist and recreational people to improve their health performance during exercise. This product is very useful where it will be explained in this report. The purpose of report is to given details and explain about the product description, technology description, market analysis and strategies and team management in this company. So, our target customer for this product is Sportsperson or athlete. Sportsperson is a person who is involved in sports. Sporting is an important part of Malaysian culture in Malaysia. Sports are popular in Malaysia from both the aspect of participation and spectacle. Malaysians from various walks of life join a wide variety of recreational and competitive sports. Other than that, in this report will discuss about the market strategies of the company, channel that has been use and market size and trend over 3 years. Advanced Foam Roller with TENS SDN BHD is managed by seven top managements which are consists of ECO, General Manager, Operating Manager, Marketing manager, Operational manager, Administrative Manager and lastly is R&D Executive Software Developer Engineer. We are the first Malaysia company that produce product we believe that it can be our added values and remain competitive to other existing vibrating foam roller manufacturer.